THE CORRELATION BETWEEN THE SEVERITY OF DENTAL CARIES AND THE QUALITY OF LIFE OF TEENAGE GIRLS IN ORPHANAGES IN BANJARMASIN - Erlis Tiana Safitri; Galuh Dwinta Sari; Isnur Hatta (FKG Unlam, 2023)
Background: Teenagers experience an increase of caries rate every year, such as the rate of 4.9 in 2013 increased to 7.2 in 2018. The caries rate by female teenagers tends to be higher than the male's rate of 7.2 in number. Adolescents, especially female teenagers, have a high sensitivity to the perfection of their physical appearance and attractiveness so that the high caries rate can be a negative influence on their quality of life. Purpose: To analyze the relationship between the severity of caries and the quality of life teenage girls in female orphanages in Banjarmasin. Methods: The method that was used in this study was observational analytic with the implementation of a cross sectional approach. The samples were taken by using simple random sampling techniques with a cross sectional sample formula being applied, obtaining 42 respondents. The data were collected by using the DMF-T index measurement instrument and the Indonesian version of COHIP-SF 19 questionnaire which had been tested for validity and reliability tests. Results: The results of Rank-Spearman test data analysis obtained the significant value of 0.000 (p<0.05) which means the level of dental caries of teenage girls in the orphanages with their quality of life related to dental and oral health had a significant relation, the correlation value that was obtained was 0.531, which means the strength of the correlation was strong toward the positive direction correlation (unidirectional). Conclusion: There is a correlation between the severity of dental caries and the quality of life of teenage girls in the orphanages. Keywords : Caries, orphanage, quality of life, teenage girl